High PRF Metal Vapor Brightness Amplifiers: Research and Applications - Evtushenko G. S. Gennady Sergeevich; Trigub M. V. Maksim Viktorovich; Torgaev S. N. Stanislav Nikolaevich; Musorov I. S. Ilia Sergeevich; Drobchik V. V. Vitaly Viktorovich; Kulagin A. E. Anton Evgenievich (2016, 2016)
Title screen